2008
DOI: 10.2172/939046
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vadose Zone Sediments Below the T Tank Farm: Boreholes C4104, C4105, 299-W10-196, and RCRA Borehole 299-W11-39

Abstract: Executive SummaryThis report was revised in September 2008 to remove acid-extractable sodium data from Tables 4.8, 4.28, and 4.52. The sodium data was removed due to potential contamination introduced during the acid extraction process. The rest of the text remains unchanged from the original report issued in September 2004.The overall goal of the Tank Farm Vadose Zone Project, led by CH2M HILL Hanford Group, Inc., is to define risks from past and future single-shell tank farm activities at Hanford. To meet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 21 publications
(75 reference statements)
1
23
0
Order By: Relevance
“…The uranium concentrations in Boring C3832 pore water, derived from water extracts (1:1 by mass) peaked at 2850 µg/L within the Upper Cold Creek Unit (Serne et al 2004a). The uranium concentrations in Boring C4104 derived from sediment:water extracts reached 17,800 µg/L and peaked just above the Upper Cold Creek Unit (Serne et al 2004b). Only low levels (less than 2 µg/L) of uranium were detected in the groundwater samples from wells near these two borings, and low U-236/U-238 ratios (<5.1x10 -7 ) indicated less than 1% contaminant contribution to the groundwater uranium.…”
Section: 15mentioning
confidence: 92%
“…The uranium concentrations in Boring C3832 pore water, derived from water extracts (1:1 by mass) peaked at 2850 µg/L within the Upper Cold Creek Unit (Serne et al 2004a). The uranium concentrations in Boring C4104 derived from sediment:water extracts reached 17,800 µg/L and peaked just above the Upper Cold Creek Unit (Serne et al 2004b). Only low levels (less than 2 µg/L) of uranium were detected in the groundwater samples from wells near these two borings, and low U-236/U-238 ratios (<5.1x10 -7 ) indicated less than 1% contaminant contribution to the groundwater uranium.…”
Section: 15mentioning
confidence: 92%
“…The mineralogy in sediments from the BX and TX Tank Farm boreholes were characterized in other studies (Serne et al 2008a(Serne et al , 2008b. This characterization was conducted in the same BX-102 borehole as sediments 1 and 2 in this study (and similar depths, as shown in Tables 3.1 and 3.2).…”
Section: Sediments Used In Studymentioning
confidence: 92%
“…In this study, the calcite content of the mixture of sediments 3a and 3b should average ~1% (Table 3.2), so other than this calcite content, the higher clay content of the Cold Creek and Hanford formation sediments at the TX Tank Farm (8% to 10%, compared to 2.5% to 5.5%) could result in higher reactivity for sediment 3 compared to sediments 1 and 2. Serne et al (2008aSerne et al ( , 2008b.…”
Section: Sediments Used In Studymentioning
confidence: 99%
“…Due to sample mass limitations, no analyses could be performed on material recovered from the shoe in push hole C5170. It has been well documented in several borehole reports that uncontaminated Hanford sediments have soil pH values ranging from 7.0 to 8.0 (Serne et al 2002a(Serne et al , 2004bLindenmeier et al 2003;Brown et al 2006). Sediment pH values are considered slightly elevated between 8.0 and 8.5 and are significantly elevated above 8.5.…”
Section: Ph and Electrical Conductivitymentioning
confidence: 96%